Curriculum Development For 21st Century Skills: Trends, Challenges, and Solutions - Hasibuan, Kalayo; Ledy, Aisan; Az-Zahra, Fathia Zawatha (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Curriculum development for 21st century skills is becoming an important focus in global education. This article explores key trends such as technology integration, project-based learning and cross-disciplinary approaches. Challenges include limited infrastructure, resistance to change and the need for adequate teacher training. Through literature analysis and case studies, strategic solutions such as policy alignment, collaboration between stakeholders and the adoption of innovative technologies are proposed to overcome these obstacles. This article highlights the importance of a holistic approach in crafting a curriculum that is relevant to the needs of modern society, ensuring students have skills such as critical thinking, collaboration and digital literacy. The findings provide guidance for educators, policymakers and researchers in designing adaptive and sustainable education.